Postmodern thinking in discourses on the practice of design - Pittaluga, Mariana (Universidad de Lima. Carrera de Arquitectura, 2019)
This paper aims to demonstrate the influence of postmodern discourses on new discourses on the practice of design. By understanding the design as a product of modernity, we assume that the crisis of this cultural construction also breaks down the corpus of discourses on the practice of design, giving rise to new positions and arguments which, at the same time, modify the practice itself and determine the expansion of its field. Taking philosophy as a starting point to understand the debate on modernity-postmodernity, we analyze its influences and shades according to the most influential authors in the field of design.